1993
DOI: 10.1039/ft9938903635
|View full text |Cite
|
Sign up to set email alerts
|

Vapour-phase oxidation of diamond surfaces in O2 studied by diffuse reflectance Fourier-transform infrared and temperture-programmed desorption spectroscopy

Abstract: Thermal oxidizing treatments of hydrogenated diamond surfaces have been performed in an O2 environment.Chemisorption of oxygen on diamond surfaces has been investigated by diffuse reflectance Fourier-transform infrared (FTIR), temperature-programmed desorption (TPD), temperature-programmed reaction (TPR) and thermogravimetry (TG). Oxidation of the hydrogenated diamond occurred above 300 "C and diamond started to burn out above 480 "C in 20% 0,. Diffuse reflectance FTIR spectra indicated that the oxidation gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
130
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 20 publications
7
130
0
Order By: Relevance
“…A previous study reported that the surface of diamond behaves as an organic substance in certain chemical reactions. 36 The diamond surface is expected to have possibility of chemical reactivates as an organic substance.…”
Section: -30mentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that the surface of diamond behaves as an organic substance in certain chemical reactions. 36 The diamond surface is expected to have possibility of chemical reactivates as an organic substance.…”
Section: -30mentioning
confidence: 99%
“…A previous study reported that the surface of diamond behaves as an organic substance in certain chemical reactions. 36 The diamond surface is expected to have possibility of chemical reactivates as an organic substance.37 These findings led us to develop a novel utilization of diamond as a material of a catalyst or as a catalyst support for chemical reactions.To date, several scholars have focused on the diamond series, such as diamond electrodes, 38,39 and modified electrodes that use various types of diamonds, 40,41 but only a few studies on electrochemical sensors for diamond powder (DMP) detection of BPA and BPS have been reported. DMP is a pure carbon material with abundant negative charge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Maki et al studied the hydrogenation of diamond surfaces by hydrogen gas at temperatures above 700 C, 1) but this is a costly process for industrial applications because of the special attention to reactive hydrogen at high temperatures. Also, oxidations of diamond at high temperatures, 2) or by acid treatment 3) were studied. Tsubota et al reported a method to reform oxidized diamond surfaces with silane coupling agents.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond surface is easily oxidized by oxidative acids such as HNO3, HClO, H2O2, etc., and is also oxidized by O2 at high temperatures to form C _ O _ C ether type structures and C=O carbonyl type structure 12) . Transition metals loaded on various metal oxide supports exhibit metal support interactions and sometimes form binary oxides 13) 16) .…”
Section: Introductionmentioning
confidence: 99%